RESISTANCE OF BACTERIA OF THE GENUS LACTOBACILLUS TO THE METABOLITES OF THE DIGESTIVE SYSTEM - Ю. М. Похилько; Н. О. Кравченко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2017)
Aim. The purpose of this study was to determine the effect of the pH of metabolites in the digestive system on the growth activity of lactic acid bacteria isolated from the gastrointestinal tract of rabbits. Methods. The paper used 11 strains of lactic acid bacteria isolated from the gastrointestinal tract of rabbits. Stability of bacteria to the metabolites of the digestive system was determined by culturing them in MRS medium with bile, hydrogen chloride, sodium chloride, phenol. Results. It was found that the strains studied survived at a pH of 4.0 to 9.0. All the strains had high resistance to bile concentration (20, 40%), hydrogen chloride (3%), sodium chloride (5%), phenol (0.5%), viable cells - 103–105 CFU / ml after 48 hours cultivation. Conclusions. It was found that the studied strains of lactobacilli were resistant to high concentrations of bile and phenol, 70% to low pH, 50% to sodium chloride, and 20% to hydrogen chloride.